#TITLE_ALTERNATIVE# - ANDIKA PUTRI (NIM 15107036); Pembimbing: Dr. Deni Suwardhi, ST., MT. dan Ir. Agoes Soewandito, NINDYA
These last few years, the development towards a better level of detail of three-dimensional (3D) modeling of building increase rapidly. 3D modeling has reached the Level of Detail (LOD) 4 in which the room interior and the objects or furniture in it are also displayed. In terms of mapping, to create a 3D model of an object, the measurement or data acquisition on the object must be done to obtain the form as they should be in the field. For the purposes of construction, the measurement of interior has a standard of tolerance that must be met. There is a simple and low-risk method for measuring the dimensions of a plane that has been applied by several researchers. The method used is a close range photogrammetry measurement method based on single image and assisted with distometer/laser distance meter. Cameras and distometer are combined and placed in a certain support. Images of the object are taken using a camera and the distance of the camera to the object is measured using distometer. In this research, the method is applied to the measurement of room interior. However, after the experiments, it is known that this method can not obtain good result of interior dimensions and the interior has not been able to model in 3D yet.